148 The effect of natalizumab and interferon-β on urinary free light chains and anti-EBV nuclear antigen-1 antibodies in relapsing remitting multiple sclerosis. Issue 3 (9th February 2012) - Raffel, J; Dobson, R; Giovannoni, G
Abstract : Background: Epstein-Barr Virus (EBV) has been associated with multiple sclerosis (MS), but its role in disease pathogenesis has yet to be confirmed. B cells are also implicated in MS, and urinary free light chains (uFLC)—a marker of B cell activity—are known to be raised in MS. Objectives: To investigate how MS medications affect B cell and anti-viral activity in patients with relapsing remitting MS (pwMS). Methods: In a cross-sectional study, 20 pwMS established on natalizumab were compared with 11 pwMS on interferon-β, and 18 untreated pwMS. uFLC, serum anti-EBNA-1, anti-CMV and anti-VZV IgG were measured using ELISA. uFLC were expressed as a ratio to urinary protein in order to correct for variable urine concentrations. Results: Anti-EBNA-1 IgG levels were significantly lower in pwMS on interferon-β compared with untreated pwMS (p=0.02), but there was no such effect on anti-CMV or anti-VZV IgG. There was no difference between the natalizumab and either the untreated or the interferon group in anti-EBNA-1, anti-CMV, or anti-VZV IgG levels. uFLC levels were equal in all three groups. uFLC levels correlated with anti-EBNA-1 IgG levels across the study population (Spearman's correlation coefficient =0.327; p=0.048). Conclusions: These data suggest that interferon-β decreases anti-EBV activity in pwMS. These data also support a link between EBV activity and B cell activity in MS. Further prospective studies are required to confirm these observations.